2021
DOI: 10.5713/ajas.20.0116
|View full text |Cite
|
Sign up to set email alerts
|

Production performances and antioxidant activities of laying hens fed Aspergillus oryzae and phytase co-fermented wheat bran

Abstract: Objective: Wheat bran (WB) was co-fermented with Aspergillus oryzae and phytase (Phy) to determine whether co-fermentation improve WB phosphorus and fiber utilization in Isa-brown layers.Methods: A total of 112 Isa brown layer were randomly divided into 7 treatments with 8 replicates per a treatment and 2 hens per a replicate. The treatments included basal diet (control), basal diet supplemented with 250 unit/kg Phy (control+Phy), diet with 10% WB (10% WB), diet with 5% WB and 250 unit/kg Phy (5% WB+Phy) diet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…Phosphoric acid on inositol can combine with minerals or amino acids of valence 2 or 3 and reduce the absorption rate of nutrients and enzyme activity of animals [49][50][51][52]. In addition, the involvement of too much phytic acid may also lead to poor phosphorus utilization by animals, causing the accumulation of phosphorus in stool and this may cause pollution to the environment [53]. Fortunately, phytic acid can be degraded by phytase.…”
Section: Phytic Acidsmentioning
confidence: 99%
See 2 more Smart Citations
“…Phosphoric acid on inositol can combine with minerals or amino acids of valence 2 or 3 and reduce the absorption rate of nutrients and enzyme activity of animals [49][50][51][52]. In addition, the involvement of too much phytic acid may also lead to poor phosphorus utilization by animals, causing the accumulation of phosphorus in stool and this may cause pollution to the environment [53]. Fortunately, phytic acid can be degraded by phytase.…”
Section: Phytic Acidsmentioning
confidence: 99%
“…and Bacillus subtilis [99]. After fermentation, cellulose and lignin content decrease, while hemicellulose and extractable functional metabolites increase slightly [3,53]. However, other crude ingredients, such as crude protein and minerals, are concentrated [53].…”
Section: Solid-state and Liquid Fermentationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Probiotics such as Lactobacillus, Saccharomyces, and Bacillus subtilis have been widely used in feed fermentation, but it has been shown that the amount of protease secreted by the strains through simple microbial fermentation alone is low and cannot meet the actual production demand (7). Bacterial and enzyme co-fermented feed refers to the addition of a certain amount of exogenous compound enzymes and probiotics for joint fermentation, thus degrading the anti-nutritional ingredients in the feed, regulating the bitterness of the feed, improving the palatability of the feed, compensating for the lack of enzyme production and poor enzymatic taste of a single microbial fermentation, promoting animal feeding, improving feed utilization and nutritional value (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Fermented feed can fully utilize unconventional feed to compensate for feed material shortages and enhance the culture environment, both of which are crucial for the breeding of laying hens without the use of antibiotics. Fermented feed has a certain favorable impact on the intestinal flora and host health ( Guo et al, 2021 ), increases the amount of lactic acid bacteria and the concentration of SCFAs in feces, improves intestinal digestive and metabolic activities, promotes antioxidant and anti-inflammatory effects, and enhances the production performance and egg quality of laying hens ( Huang et al, 2020 ; Li et al, 2020 ; Zhu et al, 2022 ). The gastrointestinal tract is a complex environment ( Kelly and Conway, 2001 ; Wei et al, 2013 ), and both the feeding environment and its health status affect the composition of intestinal microbes ( Wilson et al, 2005 ).…”
Section: Introductionmentioning
confidence: 99%